Model Inkuiri Terbimbing dengan Pemanfaatan Aplikasi Simulasi Interaktif Sebagai Strategi Pembelajaran untuk Meningkatkan Penguasaan Konsep Gelombang Bunyi - Tehuayo, Hobertina Melinda; Wattimena, Herman Samuel; Tamaela, Elsina Sarah; Napirah, Mardiana (Pattimura University, 2024)
Students' understanding of the concept of sound waves is still a challenge in learning physics because it is abstract and requires active involvement in the scientific thinking process. This study aims to analyze the effectiveness of the guided inquiry learning model by utilizing interactive simulation applications as an innovative learning strategy in improving the mastery of the concept of sound waves in students of class XI IPA-2 SMA Negeri 8 Maluku Tengah. The research design used was a one-group pretest-posttest involving 25 randomly selected students. The research instruments included tests (pretest and posttest) and non-tests in the form of Learner Worksheets (LKPD) designed to encourage the inquiry process. The pretest results showed that all learners (100%) were in the failing category with an average score of 5.8. After the application of the model, the average score of students increased to 75.7 in the posttest and 77.4 during the learning process, both in the sufficient category. The N-Gain test results showed an average improvement score of 0.71 (high category). All students also managed to achieve scores above the KKM (≥70) for all indicators of competency achievement. These results indicate that the application of the guided inquiry model is not only effective, but also relevant to today's learning needs that demand critical and exploratory thinking skills. This research contributes to strengthening the role of the guided inquiry model as an adaptive learning approach for conceptual physics topics.